Synthesis and characterization of Graphene - ZnO NPs nanocomposite and its application for antibacterial activities - Solmaz Abdollahi; Afshin Pourahmad; Leila Asadpour (Fasa University of Medical Sciences, 2018)
Background & Objective: The investigation of the antibacterial activity of nanomaterials has regained importance due to increasing bacterial resistance to antibiotics. Inorganic antibacterial materials have several advantages over traditionally used organic agents; like chemical stability, thermal resistance, safety to the user, long lasting action period, etc. In this research, antibacterial properties of graphene - zinc oxide nanoparticles nanocomposite was evaluated for gram-positive (S. aureus) and gram-negative (E. coli and Pseudomonas aeruginosa) bacteria. Material & Methods: The current study demonstrates homogenous decorating of zinc oxide nanoparticles (NPs) onto graphene oxide (GO) surface via simple chemical method. Disk diffusion method and MIC were used to evaluate the antibacterial activity of ZnO nanoparticles on S. aureus, E. coli and Pseudomonas aeruginosa compared to standard commercial antibiotic disks. Results: XRD results revealed diffraction peaks for each of the two compounds in the nanocomposite. The XRD studies showed that the synthesized ZnO NPs have hexagonal wurtzite structure. It was found that GO addition induces a decrease in crystallite size. Average size of the ZnO NPs was estimated by transmission electron microscopy around 20 nm. ZnO nanoparticles showed bactericidal effects on Gram-positive and Gram-negative bacteria. The improved antibacterial activity of ZnO nanoparticles compared to its microparticles was related to the surface area enhancement in the nanoparticles. Conclusions: The novel nanocomposite exhibits excellent antibacterial activity against gram-positive (S. aureus) and gram-negative (E. coli and Pseudomonas aeruginosa) bacteria.